Crime, Deterrence and the Business Cycle in New York City: A VAR Approach - Corman, Hope; Joyce, Theodore; Lovitch, Norman (The Review of Economics and Statistics, 1987)
Hope Corman, Theodore Joyce, Norman Lovitch, Crime, Deterrence and the Business Cycle in New York City: A VAR Approach, The Review of Economics and Statistics, Vol. 69, No. 4 (Nov., 1987), pp. 695-700